Bibliography on neotropical fruits - Libreros, D.; International Plant Genetic Resources Institute (2000)
A great diversity of fruit species has originated in the American tropics. Despite their many uses - including fresh consumption, animal feeding, agribusiness and crop diversification - just a few Neotropical fruits have been studied. This makes bibliography scarce, scattered and not easily accessible to fruit crop researchers. Scientists searching for information on Neotropical fruit species frequently have to look at various sources yet rarely find what they are looking for. During the past few years, the IPGRI Americas Group has conducted a number of research projects on fruits native to the Americas for which bibliographic references have been gathered. This bibliography is the result of that activity. Researchers, university professors and students can now use these resources to assess the state of the art of some species and identify information gaps in others. Available in electronic form only as a Portable Document Format (PDF) file.